DAMPAK JUMLAH PELANGGAN DAN PENAMBAHAN INVESTASI JARINGAN PERUSAHAAN TELEKOMUNIKASI TERHADAP INFLASI (STUDI KASUS INDOSAT OOREDOO) - Milla Naeruz (JRMB (Jurnal Riset Manajemen & Bisnis), 2018)
The increase in the price of subsidized fuel oil by Rp 2,000 per liter can increase inflation to a higher level. This issue was responded by telecommunication entrpreneurs such as PT Indosat Tbk (ISAT) which perceives that this condition can affect their financial performance as additional cost and this can reduce profits.To support future expansion and strategy, Indosat Ooredoo will continue to increase the number of Base Transceiver Station (BTS) to improve services to customers. The total number of Indosat Ooredoo BTSs at the end of 2017 was 61,357, the number of Indosat Ooredoo cellular customers in 2017 reached 110.2 million, but Indosat's revenue decreased from 15 trillion to 11 trillion in 2018. Nevertheless this study is to investigate whether the number of customers and the number of networks give influence to inflation in Indonesia. This study uses microeconomics theory and management relate to inflation, customers and investment. The method was a quantitative approach using secondary and numerical data in the form of a time series; journal, previous research results and other relevant reading resources to this study. The dependent variable is inflation while the independent variables are the number of customers and the number of investation of Base Transceiver Stations/Network Investment.  This study uses Eviews 10 while the results of this study that the number of customers as well as network investment respectively has a negative and insignificant influences to inflation.  The increase in the price of subsidized fuel oil by Rp 2,000 per liter can increase inflation to a higher level. This issue was responded by telecommunication entrpreneurs such as PT Indosat Tbk (ISAT) which perceives that this condition can affect their financial performance as additional cost and this can reduce profits. To support future expansion and strategy, Indosat Ooredoo will continue to increase the number of Base Transceiver Station (BTS) to improve services to customers. The total number of Indosat Ooredoo BTSs at the end of 2017 was 61,357, the number of Indosat Ooredoo cellular customers in 2017 reached 110.2 million, but Indosat's revenue decreased from 15 trillion to 11 trillion in 2018. Nevertheless this study is to investigate whether the number of customers and the number of networks give influence to inflation in Indonesia. This study uses microeconomics theory and management relate to inflation, customers and investment. The method was a quantitative approach using secondary and numerical data in the form of a time series; journal, previous research results and other relevant reading resources to this study. The dependent variable is inflation while the independent variables are the number of customers and the number of investation of Base Transceiver Stations/Network Investment.  This study uses Eviews 10 while the results of this study that the number of customers as well as network investment respectively has a negative and insignificant influences to inflation.